Как сделать урок интересным - Кадомцева, Э. Р.; Лазарева, А. Н.
Тема “Односоставные предложения” - одна из непростых в синтаксисе. Автор предлагает описание урока в девятом классе с использованием презентации и видеоролика при объяснении новой темы. Форма работы учащихся – индивидуальная, фронтальная и групповая. Используя различные методы и приемы на уроках русского языка, учитель создает условия для интеллектуального развития учащихся и атмосферу сотрудничества и сотворчества. “One-member sentences" is one of the most complicated topics in syntax. A description of a lesson with the use of a video clip and a presentation is suggested to the attention of teachers for the explanation of a new topic in the 9th form. The form of the work of the pupils is individual, face-to-face and group. The teacher must create conditions for the intellectual development of pupils using various methods and techniques in the Russian language lessons, and, also create an atmosphere where learning occurs in collaboration and co-creation. Միակազմ նախադասությունները շարահյուսության ոչ հեշտ թեմաներից են: Առաջարկվում է 9-րդ դասարանում նոր նյութի բացատրման դասի նկարագրությունը պրեզենտացիայի և տեսահոլովակի օգտագործմամբ, անհատական և խմբային աշխատանքի ձևեր: Ռուսաց լեզվի դասի ընթացքում զանազան մեթոդների և հնարքների օգտագործմամբ ուսուցիչը պայմաններ է ստեղծում սովորողների ինտելեկտի զարգացումը և իրականացվում է համագործակցական և համատեղ ստեղծագործելու միջավայր: In this article two types of lessons are reviewed as basis of technological component of modernization of educational practice. Thoroughly is reviewed the lesson with guaranteed result, built on the basis of systematic formation of mental actions. Ключевые слова. Технологический подход к модернизации практики образования, гарантированный результат урока, результатный урок, образовательная среда урока, средовой урок
Keywords: Практика